Answer:
Step-by-step explanation:
log3^(2x+3) = log243
(2x+3)log3 = log243
2x+3 = log243/log3
2x = (log243/log3)-3
x = [(log243/log3)-3]/2
x = (5-3)/2
x = 2/2
x = 1
Check:
3^2(1)+3 = 243
3^2+3 = 243
3^5 = 243
3×3×3×3×3 = 243
9×9×3 = 243
81×3 = 243
243 = 243
Answer:
x as a fraction: 11![\frac{1}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D)
Step-by-step explanation:
Variable x cannot be equal to −2 since division by zero is not defined. Multiply both sides of the equation by 9(x+2), the least common multiple of 9,x+2.
2 ( x+ 2) = 9 x 3
Use the distributive property to multiply 2 by x + 2.
2x + 4 = 9 x 3
Multiply 9 and 3 to get 27.
2x + 4 = 27
Subtract 4 from both sides.
2x = 27 - 4
Subtract 4 from 27 to get 23.
2x = 23
Divide both sides by 2.
x = ![\frac{23}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B23%7D%7B2%7D)
Simplify
11![\frac{1}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D)
Hope it helps and have a great day! =D
~sunshine~
Answer:
x= -5.5
Step-by-step explanation:
We actually don't need to do any computation. By definition, the inverse function
changes the role of input and output. So, if a function f maps x onto y, the inverse function maps y onto x.
You have to think like this: if the function makes a step further, the inverse function makes that same step back.
This means that the composition
is always the identity function
. In fact,
![(f\circ f^{-1})(x) = f(f^{-1}(x)) = x](https://tex.z-dn.net/?f=%20%28f%5Ccirc%20f%5E%7B-1%7D%29%28x%29%20%3D%20f%28f%5E%7B-1%7D%28x%29%29%20%3D%20x%20)
So, for every function, you have
![(f\circ f^{-1})(4) = f(f^{-1}(4)) = 4](https://tex.z-dn.net/?f=%20%28f%5Ccirc%20f%5E%7B-1%7D%29%284%29%20%3D%20f%28f%5E%7B-1%7D%284%29%29%20%3D%204%20)
52m when m= 105
52(105)
5,460
so you plug in the 105 next to the 52 and you multiply it and get 5,460.
i hope this helped